FUNGSI MUSIK NDOTO DALAM RITUAL NGAGHA MERE - Blandina Wenika Djawa (Institut Seni Indonesia Yogyakarta, 2019)
Ndoto is one of the musical instruments that is quite important in the Ngagha Mere ritual, a ritual of giving thanks and giving sweet potato as an offering to the ancestors, namely ine ebu kaju, by the Wajo people in Nagekeo District, Flores, East Nusa Tenggara. The importance of Ndoto's function in rituals also did not allow the indigenous people to play after the ceremony was completed and even the photos had to be split and burned to become a source of fire for Sweet Potatoes. This fact becomes an interesting phenomenon to be explored.The phenomenon of making photographs that should not be played and become a source of fire in the ritual procession of Ngagha Mere in the context of culture is a case of problems so that this type of research uses qualitative case studies with data collection techniques in the form of observation and interviews.The results show that the function ndoto in the Ngagha Mere ritual is a means of communication.